O mało znanym sposobie popularyzacji zabytków archeologicznych w czasach PRL-u - Kłosińska, Elżbieta Małgorzata (Muzeum Okręgowe w Rzeszowie, 2023)
During the PRL period, craftsmen and artists from cooperative companies producing household items (e.g., from the Rzut Cooperative in Toruń) created a collection of replicas of ceramics, mainly from the Lusatian culture, in response to the growing interest in archaeological research (e.g., in Biskupin). This pottery collection enjoyed great popularity and contributed to the popularization of archaeology in Polish society.
On a little-known way of popularizing archaeological artefacts during the PRL period
Keywords: popularizing archaeology; PRL; replicas of Lusatian culture ceramics